EVALUATION OF CHICKPEA GERMPLASM (DESI) (CICER ARIETINUM L.) FOR YIELD AND YIELD CONTRIBUTING TRAITS - OVAIS HAMID PEERZADA,; CHAURASIA A. K,; NAQUESHBANDI IRSHAD AHMAD, (The Bioscan, 2014)
Thirty six genotypes of chickpea were evaluated to study the magnitude of genetic variability, heritability and genetic advance in yield and yield contributing characters. The genotype RKG135 recorded highest mean performance (94.60) for number of pods/plant and biological yield / plant (g) (38.83) while genotype NBeG 13 recorded highest mean performance (56.67) for plant height. Highest mean performance for seed yield q/ha (19.61) was recorded ingenotype RVSSG 1 while genotype H 04-75 recorded highest mean performance (126.33) for days to maturity. Genotype BG 3004 showed highest mean performance for100 seed weight (28.85) and No. of branches / plant (5.00) and BGD 1053 recorded highest mean performance (19.93) for protein content. High genotypic (31.68) and phenotypic (31.82) co-efficients of variance were recorded for number of pods per plant. High heritability (99.8) coupled with high genetic advance (52.19) were recorded for seed yield q/haand highest genetic gain (64.97) was recorded for No. of pods/plant. Hence these characters indicate the presence of a considerable proportion of total variability due to genetic causes and may serve as effective selection parameter during breeding program for crop improvement.